The determinants of corporate voluntary disclosure policy: Evidence from the Abu Dhabi Securities Exchange (ADX). Issue 2 (2nd May 2017) - Kolsi, Mohamed Chakib
Abstract : Purpose: The purpose of this paper is to identify the factors affecting firm voluntary disclosure policy adopted by a sample of 25 UAE companies listed on the Abu Dhabi Securities Exchange (ADX) for the period 2010-2014. Design/methodology/approach: The author computes a weighted disclosure index (Botosan, 1997) for three-factor voluntary disclosure items and uses a multivariate regression analysis between disclosure index and a set of explanatory variables identified by previous research. The author also controls for endogeneity problem and uses panel data estimation. Findings: It has been found that listing history, governmental sector, firm profitability and foreign listing positively affect the level of voluntary disclosure adopted by ADX listed companies. By contrast, the percentage of shares owned by block holders and industrial sector negatively affect the level of voluntary disclosure by ADX listed companies. Finally, the board and firm size, managers' stock options and the leverage ratio do not have any impact on the level of voluntary disclosure adopted by ADX firms. The results remain unchanged to additional sensitivity checks. Research limitations/implications: The research presents some limitations: first, the author does not take into account all voluntary disclosure items such as human resources and environmental data disclosed by ADX listed firms. Second, other voluntary disclosure determinants remain unexplored for UAE firms such as culture and tax incentives in the light of the new tax rules including corporate tax and value-added tax. Practical implications: The study has many implications: first, it can help investors in their decision making and lead to fair allocation of resources. Second, it gives helpful directives to UAE accounting authorities to enhance the quality of financial reporting in the light of the New Commercial Company Law 2015 for mandatory adoption of IFRS by all listed companies. The paper also presents helpful directives for tax authorities planning for both company and value-added taxes. It also sheds light on factors driving corporate social responsibility disclosures as a crucial component of voluntary disclosure policy Originality/value: The paper explores the new determinants of voluntary disclosure such as foreign listing, governmental status and block holding for an emerging relatively unexplored stock market: ADX.